Discovery of a small molecule inhibitor of cullin neddylation that triggers ER stress to induce autophagy - Yanan Li (Elsevier, 2021)
Protein neddylation is catalyzed by a three-enzyme cascade, namely an E1 NEDD8-activating enzyme (NAE), one of two E2 NEDD8 conjugation enzymes and one of several E3 NEDD8 ligases. The physiological substrates of neddylation are the family members of cullin, the scaffold component of cullin RING ligases (CRLs). Currently, a potent E1 inhibitor, MLN4924, also known as pevonedistat, is in several clinical trials for anti-cancer therapy. Here we report the discovery, through virtual screening and structural modifications, of a small molecule compound HA-1141 that directly binds to NAE in both in vitro and in vivo assays and effectively inhibits neddylation of cullins 1–5. Surprisingly, unlike MLN4924, HA-1141 also triggers non-canonical endoplasmic reticulum (ER) stress and PKR-mediated terminal integrated stress response (ISR) to activate ATF4 at an early stage, and to inhibit protein synthesis and mTORC1 activity at a later stage, eventually leading to autophagy induction. Biologically, HA-1141 suppresses growth and survival of cultured lung cancer cells and tumor growth in in vivo xenograft lung cancer models at a well-tolerated dose. Taken together, our study has identified a small molecule compound with the dual activities of blocking neddylation and triggering ER stress, leading to growth suppression of cancer cells.